Quantum inspired evolutionary programming optimization technique for optimal network reconfiguration approach in distribution system / Mohamad Nazrin Mohamad Najib - Mohamad Najib, Mohamad Nazrin (2013)
This paper presents an optimization technique used to identify optimal network reconfiguration. Network reconfiguration is performed by altering the topological structure of the distribution feeder. It provides an efficient way to control the tie-line and sectionalizing switches. By reconfiguring the network, voltage stability can be improved and at the same time system total losses can also be minimized for particular set of loads in a distribution system. This however, due to its difficulties on optimizing technique that has been long used to developed, adopted as well as to improve this particular application, the proposed technique was developed based on the hybridization of quantum mechanics concepts with the Evolutionary Programming (EP) optimization and it is named as Quantum-inspired Evolutionary Programming (QI-EP). This paper utilized IEEE 69- bus system in this research. Other than minimizes the loss and stabilizes the voltage in network reconfiguration system, the research also study the performance of Quantum-inspired Evolutionary Programming (QI-EP) and identify which is the best loss minimization technique for optimal network reconfiguration.